2011
DOI: 10.1038/cr.2011.202
|View full text |Cite
|
Sign up to set email alerts
|

Differing and isoform-specific roles for the formin DIAPH3 in plasma membrane blebbing and filopodia formation

Abstract: Plasma membrane (PM) blebs are dynamic actin-rich cell protrusions that occur, e.g., during cytokinesis, amoeboid cell motility and cell attachment. Using a targeted siRNA screen against 21 actin nucleation factors, we identify a novel and essential role of the human diaphanous formin DIAPH3 in PM blebbing during cell adhesion. Suppression of DIAPH3 inhibited blebbing to promote rapid cell spreading involving β1-integrin. Multiple isoforms of DIAPH3 were detected on the mRNA and protein level of which isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
(70 reference statements)
1
23
1
Order By: Relevance
“…In addition to the activation of ezrin, active RhoA also activates another RhoA effector protein, formins, which are essential for the regrowth of actin filaments at the retracting membrane. 18,19 In the expanding phase of membrane blebs, we found that Rnd3 is recruited to the expanding plasma membrane. The membrane localization of Rnd3 was gradually lost when reassembly of actin filaments started (Fig.…”
Section: Rhoa-rock-rnd3 Feedback Loop Regulates the Expansion And Retmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to the activation of ezrin, active RhoA also activates another RhoA effector protein, formins, which are essential for the regrowth of actin filaments at the retracting membrane. 18,19 In the expanding phase of membrane blebs, we found that Rnd3 is recruited to the expanding plasma membrane. The membrane localization of Rnd3 was gradually lost when reassembly of actin filaments started (Fig.…”
Section: Rhoa-rock-rnd3 Feedback Loop Regulates the Expansion And Retmentioning
confidence: 85%
“…Subsequently, Stastna et al and Bovellan et al demonstrated that formin family proteins, key regulators of actin nucleation, are recruited to the membrane blebs and essential for the reassembly of actin filaments. 18,19 In addition, Logue et al showed that Eps8, a plus end capping protein, is recruited to the plasma membrane on a similar timescale as ezrin and essential for the formation of membrane blebs. 20 Thus, important regulators of actin cortex during membrane blebs were identified; however how these proteins are coordinated during reassembly of actin filaments in membrane blebs has remained unclear.…”
Section: The Regulation Of Actin Cytoskeleton During Membrane Blebbingmentioning
confidence: 99%
“…Most formins function as effectors for Rho-GTPases and are regulated by the intramolecular binding between the Diaphanous inhibitory (DID) and autoregulatory (DAD) domains (Faix and Grosse, 2006). Formins are involved in a variety of actin-dependent membrane processes ranging from filopodia formation (Schirenbeck et al, 2005), cell spreading (Iskratsch et al, 2013), and non-apoptotic blebbing (Kitzing et al, 2007;Stastna et al, 2012) to engulfment and phagocytosis Seth et al, 2006). FMNL2 is unique among formins as it is upregulated in several metastatic cancers and is involved in cancer cell behavior and progression (Li et al, 2010;Liang et al, 2013;Zhu et al, 2011Zhu et al, , 2008, but the underlying molecular mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Formins also have essential roles in physiological processes ranging from cell motility in the immune system (Yayoshi-Yamamoto et al, 2000;Eisenmann et al, 2007;Shi et al, 2009), to gastrulation and neural tube closure (Habas et al, 2001;Sato et al, 2006;Lai et al, 2008), heart morphogenesis (Iskratsch et al, 2010;Li et al, 2011), kidney morphogenesis (Brown et al, 2010;Boyer et al, 2011a;Boyer et al, 2011b), and dendritic spine formation in neurons. Some of these functions depend on the actin nucleation and elongation activities of formins (Bartolini et al, 2008;Andrés-Delgado et al, 2010;Madrid et al, 2010;Andrés-Delgado et al, 2012;Ramabhadran et al, 2012;Stastna et al, 2012), which have been demonstrated by investigating point mutations that impair in these activities Lu et al, 2007;Ramabhadran et al, 2012). However, for many of the other in vivo functions of formins, it has not yet been determined which of their activities are required.…”
Section: Cellular Functions Of Forminsmentioning
confidence: 99%